Impact of Magnetic Resonance Lymphography on Lymphaticolvenular Anastomosis for Lower-Limb Lymphedema - Yasunaga, Yoshichika; Kinjo, Yuto; Nakajima, Yuta; Mimura, Shinei; Kobayashi, Miharu; Yuzuriha, Shunsuke; Kondoh, Shoji (Journal of Reconstructive Microsurgery, 2021)
Background Although several investigations have described the safety, utility, and precision of magnetic resonance lymphography (MRL) as a preoperative examination for lymphaticovenular anastomosis (LVA), it is unclear how much MRL assistance impacts LVA results. The present study aimed to clarify the outcome of MRL-assisted LVA for leg lymphedema using body water measurements obtained by bioelectrical impedance analysis.Methods The water reductive effect of MRL-assisted LVA in female secondary leg lymphedema patients was compared with that of non-MRL-assisted controls in this retrospective study. In the MRL-assisted group, all LVA candidates underwent MRL prior to surgery, and the lymphatic vessels to be anastomosed were primarily determined by MRL findings. The body water composition of the treated legs was assessed before LVA and at 6 months postoperatively using a multi-frequency bioelectrical impedance analyzer.Results Twenty-three patients in the MRL-assisted study group and an equal number in the non-MRL-assisted control group were analyzed. Although mean leg water volume before LVA, mean excess water volume of the affected leg before LVA, and number of anastomoses created were comparable between the groups, the water volume reduction (1.02 L versus 0.49 L; 95% confidence interval [CI]: 0.03–1.03, p < 0.05) and edema reduction rate (46.7% versus 27.2%; 95% CI: 3.7–35.5%, p < 0.05) in the MRL-assisted group were significantly greater than in controls.Conclusion Preoperative MRL-assisted lymph vessel visualization and selection appeared to significantly enhance the water reductive effect of LVA for International Society of Lymphology classification stage 2 leg lymphedema. MRL also helped to reliably identify lymphatic vessels for anastomosis. Without increasing the number of anastomoses, LVA could be performed more effectively by better detecting stagnant lymphatic vessels using MRL.
Keywords: lymphaticovenular anastomosis; magnetic resonance lymphography; bioelectrical impedance analysis